Mononuclear Phagocyte Accumulation in Visceral Tissue in HIV Encephalitis: Evidence for Increased Monocyte/Macrophage Trafficking and Altered Differentiation - Fischer, Tracy; M. Wyatt, Christina; D. D'Agati, Vivette; Croul, Sidney; McCourt, Laura; Morgello, Susan; Rappaport, Jay (Current HIV Research, 2014)
The invasion of circulating monocytes/macrophages (Mφ)s from the peripheral blood into the central nervous system (CNS) appears to play an important role in the pathogenesis of HIV dementia (HIV-D), the most severe form of HIV-associated neurocognitive disorders (HAND), often confirmed histologically as HIV encephalitis (HIVE). In order to determine if trafficking of monocytes/Mφs is exclusive to the CNS or if it also occurs in organs outside of the brain, we have focused our investigation on visceral tissues of patients with HIVE. Liver, lymph node, spleen, and kidney autopsy tissues from the same HIVE cases investigated in earlier studies were examined by immunohistochemistry for the presence of CD14, CD16, CD68, Ki-67, and HIV-1 p24 expression. Here, we report a statistically significant increase in accumulation of Mφs in kidney, spleen, and lymph node tissues in specimens from patients with HIVE. In liver, we did not observe a significant increase in parenchymal macrophage accumulation, although perivascular macrophage accumulation was consistently observed with nodular lesions in 4 of 5 HIVE cases. We also observed an absence of CD14 expression on splenic Mφs in HIVE cases, which may implicate the spleen as a potential source of increased plasma soluble CD14 in HIV infection. HIV-1 p24 expression was observed in liver, lymph node and spleen but not kidney. Interestingly, renal pathology suggestive of chronic tubulointerstitial nephritis (possibly due to chronic pyelonephritis), including tubulointerstitial scarring, chronic interstitial inflammation and focal global glomerulosclerosis, without evidence of HIV-associated nephropathy (HIVAN), was seen in four of eight HIVE cases. Focal segmental and global glomerulosclerosis with tubular dilatation and prominent interstitial inflammation, consistent with HIVAN, was observed in two of the eight cases. Abundant cells expressing monocyte/Mφ cell surface markers, CD14 and CD68, were also CD16+ and found surrounding dilated tubules and adjacent to areas of glomerulosclerosis. The finding of co-morbid HIVE and renal pathology characterized by prominent interstitial inflammation may suggest a common mechanism involving the invasion of activated monocytes/Mφs from circulation. Monocyte/Mφ invasion of visceral tissues may play an important role in the immune dysfunction as well as comorbidity in AIDS and may, therefore, provide a high value target for the design of therapeutic strategies.
Keywords: CNS